Dehydrated food waste for composting: an overview - Khalida, Aziz; Arumugam, Veknesh; Abdullah, Luqman Chuah; Abd Manaf, Latifah; Ismail, Muhammad Heikal (UPM Press, 2022)
Food waste disposal has recently received much attention worldwide due to its major impact on environmental pollution and economic costs. Using high moisture content of food waste has the highest negative environmental impact due to increased greenhouse gas emissions, odor, and leachate. Drying technologies play an important role in reducing the moisture content of food waste, which is necessary for environmental sustainability and safety. The first part of this review highlights that sun-drying is the most cost-effective drying method. However, it has not been widely recommended for food waste management due to several limitations, including the inability to control sunray temperature and the inability to control end-product quality. Thermal drying eliminates moisture from food waste quickly, preventing hydrolysis and biodegradation. Thermal dryers, such as the GAIA GC-300 dryer, and cabinet dryer fitted with a standard tray, are the best alternative to sun drying. The second part of this review highlights that dehydrated food waste products are slightly acidic (4.7–5.1), have a high electrical conductivity (EC) value (4.83–7.64 mS cm-1), with high nutrient content, due to low pH levels, dehydrated food waste is not suitable for direct use as a fertilizer for the plants. So, the dried food waste should be composted before application to the plants because the composting process will dominate the limitation of phytotoxins, anoxia, salinity, and water repellence. Trench compost can be a good choice for decomposing dried organic waste because trench compost relies solely on soil decomposing microorganisms and insects.